2017
DOI: 10.3390/foods6080057
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Astaxanthin-Rich Microalgae “Haematococcus pluvialis” and Wholemeal Flours Incorporation in Improving the Physical and Functional Properties of Cookies

Abstract: Marine-based food supplements can improve human nutrition. In an effort to modulate glycaemic response and enhance nutritional aspects, marine-derived algal food rich in astaxanthin was used in the formulation of a model food (wholemeal cookie). Astaxanthin substitution of cookies made from three flours (wheat, barley and oat) demonstrated a significant reduction in the rate of glucose released during in vitro digestion together with an increase in the total phenolic content (TPC) and antioxidant capacity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 47 publications
4
31
1
Order By: Relevance
“…The DPPH (2,2-diphenyl-1-picrylhydrazyl) assay was used to determine the antioxidant activity of the material using the method as previously described [26]. Trolox (CAS: 53188-07-1, ACROS Organics™, Morris, NJ, USA) was used as a standard to determine the antioxidant activities of the samples and all results were expressed as µmol trolox equivalent (TE) per g sample.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH (2,2-diphenyl-1-picrylhydrazyl) assay was used to determine the antioxidant activity of the material using the method as previously described [26]. Trolox (CAS: 53188-07-1, ACROS Organics™, Morris, NJ, USA) was used as a standard to determine the antioxidant activities of the samples and all results were expressed as µmol trolox equivalent (TE) per g sample.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have shown a wide acceptance for food products that are supplemented with microalgal natural pigments, given the improvements in color and antioxidant properties, e.g., chlorophyll and carotenoids from Chlorella vulgaris and Haematococcus pluvialis [59,60]. In addition, microalgae have been incorporated into dairy products as a source of bioactive and coloring compounds, with good acceptability, particularly in texture and appearance [61].…”
Section: Sensory Testmentioning
confidence: 99%
“…Good results have been obtained for whole grain cakes. In vitro digestion studies showed a decrease in glucose release proportional to the rise in astaxanthin concentrations in the cake formulation [ 114 ]. Studies performed by Mercke et al (2003) confirmed the beneficial effect of lipids on the absorption of astaxanthin.…”
Section: Astaxanthin In the Human And Animal Dietmentioning
confidence: 99%